2009
DOI: 10.2353/ajpath.2009.080766
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Laser Burn Disrupts Immune Privilege in the Eye

Abstract: Immune privilege allows for the immune protection of the eye in the absence of inflammation. Very few events are capable of overcoming the immune-privileged mechanisms in the eye. In this study, we report that retinal laser burn (RLB) abrogates immune privilege in both the burned and nonburned eye. As early as 6 hours after RLB, and as late as 56 days after RLB, antigen inoculation into the anterior chamber of the burned eye failed to induce peripheral tolerance. After RLB, aqueous humor samples harvested from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…22,54,55 In this context, it is interesting to note that (in mice) IP disruption occurs when RPE cells are damaged by laser burns. 18 This finding has raised the troubling question of whether laser-treated eyes are at increased risk of ocular inflammation, up to the collapse of eye IP.…”
Section: Ip and The Posterior Segment Of The Eyementioning
confidence: 97%
See 1 more Smart Citation
“…22,54,55 In this context, it is interesting to note that (in mice) IP disruption occurs when RPE cells are damaged by laser burns. 18 This finding has raised the troubling question of whether laser-treated eyes are at increased risk of ocular inflammation, up to the collapse of eye IP.…”
Section: Ip and The Posterior Segment Of The Eyementioning
confidence: 97%
“…For example, in mice, retinal laser burn abrogates IP in both the burned and nonburned eye. 18 Applying laser burns to scalp HFs in vitro may indicate whether laser treatment is likely to exert similar effects on human IP. Also, at least some underlying mechanisms of action could be studied in HF organ culture, but hardly in human eyes.…”
Section: Which Specific Aspects Relevant To Ocular Ip Can Be Studied mentioning
confidence: 99%
“…ACAID is characterized by the presence of regulatory T lymphocytes that suppress the delayed type hypersensitivity response to the immunizing antigen (Niederkorn and Streilein, 1983). It has been postulated that ACAID is difficult to abrogate; however, it has been recently reported that unilateral injury to one eye such as retinal laser burn (Qiao et al, 2009), ON crush or trauma in different regions of the optic pathway (Stein-Streilein, 2012), abrogate ACAID bilaterally for an extended time period. Lucas et al (2012) suggested that the substance P (an inflammatory neuropeptide) acts in the neurologic communication between the two eyes and is involved in the loss of immune regulation post-ocular trauma.…”
Section: Mechanisms Responsible For Contralateral Eye Involvementmentioning
confidence: 98%
“…It has been demonstrated that when a mouse eye is exposed to light an activation pattern of microglia (increased and thickened microglial processes) results in the contralateral undamaged retina, the authors postulating that such reaction could be immune related ( Joly et al, 2009). Another report showed that in the mouse eye, retinal laser burn abrogates the immune privilege in both the burnt and unburnt eyes (Qiao et al, 2009).…”
Section: The Contralateral Eye Is Involved In Some Experimental Glaucmentioning
confidence: 99%
“…44 However, the risk of damage to the retinal pigment epithelium was limited by choosing albino mice. Furthermore, unspecific laser controls with laser application away from retinal blood vessels were used for comparison.…”
Section: Discussionmentioning
confidence: 99%